(untitled) (International Journal of Innovative Research in Computer Science & Technology, 2022)
Energy can be produced in a variety of ways, and electricity is one of them. Hydropower plants produce electricity from water, thermal power plants produce electricity from heat, wind energy power plants produce electricity from wind, and geothermal energy plants produce electricity from surface heat. The merits, limits, and uses of the hydro power plant energy producing process were discussed in this article. Hydro power plants are one of the most well-known, efficient, and beneficial energy producing processes. Water is a cost-effective and efficient renewable energy source for power generation. Water-based energy generation has been around for decades and has shown to be a more efficient and effective way to generate power. Dammed reservoirs, run-of-river, pumped storage, in-stream technology, and new technology gravitational vortex are five types of technologies that may be employed to boost power capacity in hydro power plants. The capacity category is further broken down into big power, small power, mini power, and micro and pico hydropower. Advanced technology could not be placed since villages were not as developed as they are now; nevertheless, as villages and countries grow, they are increasingly turning to hydro power plants as a source of electricity, which is growing more popular due to its low cost and efficacy. This document gives an overview of hydroelectric power plants for generating energy, as well as information on hydropower systems and the best turbines to employ.